Strategic priorities of Kazakhstan innovative economy development - A.B., Maydirova; Sanalieva L.K., Baizholova R.A.,; G.T., Akhmetova; A.A., Kocherbaeva (Opción, 2020)
In this article we examined the strategic priorities for the development of the innovative economy of Kazakhstan. We conducted an analysis of the policy that has been carried out since 2010. We determined the goal and objectives of industrial and innovative development for 2020-2025.